Attachment style, friendship quality and the mediating effect of communication skills in young adults friendship : literature review - Lim, Ai Shin; Khoo, Elijah E.T.; Yueh, Ranon Earn (Penerbit Universiti Kebangsaan Malaysia, 2021)
Bowlby’s attachment theory (1973, 1980, 1982) postulated that the prototypes for adult attachment styles are based on their infancy experiences with the primary care-givers. Such experiences give rise to individuals’ internal working models, constituting views of self and others as a consequence of their relationships history. Internal working models are rules, schemas or scripts that sum up a person’s past experiences which will influence the quality of their close relationships developed later in life as these models determine how individuals interpret and react in social situations. To examine the relationship between the attachment styles of young adults and their friendship quality. This includes exploring how individuals’ attachment styles can affect their patterns of communication, leading to perception of friendship quality in dyadic friendship relationship. A Systematic Review Approach has been adopted to conduct this Literature Review. Electronic databases of MEDLINE/PUBmed, EMBASE, Cochrane Library were searched using MeSH terms and keywords such as “Attachment Style”, “Friendship Quality” and “Communication Skill”. Boolean operator “AND” was used to join these terms to form a full search strategy which also include the use of Scholar Google.Studies linking attachment styles, friendship quality and communication skill in young adults were included in this review while others with unrelated elaborations were excluded. Securely attached individuals usually communicate better, have higher quality friendship relationships and enjoy more intimacy and satisfaction in their relationships. They tend to self-disclose more compared to insecure individuals, leading to greater intimacy in their friendship relationships. Anxious and avoidant people who have negative view of others tend to self-disclose less, leading to lower level of intimacy in their friendship relationships. Appraisal of friendship quality involves reciprocity, self-disclosure and responsiveness from both parties. It was found that individuals’ internal working models can be reconstructed through experiences with their romantic partners, length of their friendship relationship and factors such as individuals’ age, culture and gender. Attachment styles and ethnicity of individuals played a role in their communication skills and can lead to diverse friendship quality experienced.